Turkish Islam in Africa: a Study of the Gülen Movement in Kenya - (:unkn) unknown (My University, 2012)
This paper addresses the current expansion of a religiously motivated educative movement coming from Turkey, the Fethullah Gülen movement, in Africa and more specifically in Kenya. First it will highlight the stakes raised by the definition of the movement and the nature of its action. Then it will strive to demonstrate the existence of a "joint-venture" between the Turkish state and the movement of Fethullah Gülen. Lastly it will examine the impact of the movement on Kenya, a retreating state, and the project of creating an "indigenized" elite in the country.
Keywords: African Research